Kinerja Pembinaan Dinas Sosial Kota Denpasar dalam Penanganan Prostitusi (Studi Kasus: Prostitusi di Jalan Danau Tempe) - Hadinegara Watruty, Satria Putra Pratama; Yasintha, Putu Nomy; Sastra Wijaya, Komang Adi (CITIZEN CHARTER; Vol 1 No 2 (2019), 2019)
ABSTRACT Prostitution is a social problem that tends to occur in urban areas of a country, including in Indonesia. In Denpasar, in dealing with the problem of prostitution, a government institution, namely the Social Service Office of the City of Denpasar, was given the responsibility of fostering female prostitutes again as functional citizens. The purpose of this study is determining the performance of the Denpasar City Social Service in dealing with the problem of prostitution. The research method used is Qualitative Descriptive method with the method of determining the informant is Purposive Sampling and the method of observation is Passive Observation. I t was found that the performance of the Denpasar City Social Service prostitution was still not effective due to various factors from WTS, community participation and the interests of third parties. Therefore it is recommended to educate the younger generation about the dangers of  HIV/AIDS or legalize prostitution Keywords : Performance, Prostitution, Denpasar City Social Service